2020
DOI: 10.3847/1538-4357/ab8a4a
|View full text |Cite
|
Sign up to set email alerts
|

The Angular Momentum of the Circumgalactic Medium in the TNG100 Simulation

Abstract: We present an analysis of the angular momentum content of the circumgalactic medium (CGM) using TNG100, one of the flagship runs of the IllustrisTNG project. We focus on Milky Way–mass halos (∼1012 M ⊙) at z = 0 but also analyze other masses and redshifts up to z = 5. We find that the CGM angular momentum properties are strongly correlated with the stellar angular momentum of the corresponding galaxy: the CGM surrounding high-angular momentum galaxies has a systematically hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 87 publications
5
40
0
Order By: Relevance
“…Tangential velocities were also explored using the Illustris-TNG simulations by DeFelippis et al (2020), where they also found higher cool than hot v tan that greatly increase inside 0.5R 200 for z = 0 10 11.75−12.25 M haloes. They divide their sample into quartiles based on specific stellar angular momentum, j * , and examine all L * centrals in Illustris-TNG, while excising gas bound to satellites.…”
Section: Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tangential velocities were also explored using the Illustris-TNG simulations by DeFelippis et al (2020), where they also found higher cool than hot v tan that greatly increase inside 0.5R 200 for z = 0 10 11.75−12.25 M haloes. They divide their sample into quartiles based on specific stellar angular momentum, j * , and examine all L * centrals in Illustris-TNG, while excising gas bound to satellites.…”
Section: Velocitymentioning
confidence: 99%
“…Their lowest j * quartile shows angles of ≈60 • , more similar to our results. The existence of extended CGM structures, including the CGM associated with satellites that is excised by DeFelippis et al (2020), likely biases high our angles between stars and the CGM. We therefore analyse the angular momentum alignment in our haloes after filtering out the CGM around satellites with the goal of assessing the impact of these extended CGM structures.…”
Section: Angular Momentummentioning
confidence: 99%
“…While gas accretes on to galaxies from the cosmic web filaments, outflowing gas preferentially leaves the galaxy following the path of least resistance, along its minor axis. Where they compete, galactic winds prevent infall of material from regions above and below the disc place (Brook et al 2011;Mitchell et al 2020b;DeFelippis et al 2020). As a result, inflowing gas is almost co-planar with the major axis of the galaxy (Stewart et al 2011;Shen et al 2012;.…”
mentioning
confidence: 99%
“…As disks evolve from z = 2 to the present, they must grow from a vast reservoir of corotating cold accreting material in the circumgalactic medium (CGM) as argued in Renzini (2020). This is also strongly supported by hydro-dynamical simulations which predict roughly coplanar gaseous structures (Stewart et al 2013(Stewart et al , 2017Danovich et al 2015;Ho et al 2019;Kretschmer et al 2020;DeFelippis et al 2021) embedded in a rotating CGM (DeFelippis et al 2020). These coplanar structures were initially found by Barcons et al (1995) and Steidel et al (2002) in a handful of background quasar sight-lines, but they are now routinely observed on scales of 20-80 kpc (as in Bouché et al 2013Bouché et al , 2016Ho et al 2017;Lopez et al 2018;Martin et al 2019;Zabl et al 2019).…”
Section: Introductionmentioning
confidence: 82%